Association Between HLA-DRB1 Alleles and Gravesʼ Disease in Asian Populations: A Meta-Analysis - Li, Wenyi; Ke, Tingyu; Wang, Jia; Zhu, Fangling; Chi, Yan (Hormone and Metabolic Research, 2024)
Graves’ disease (GD) is an autoimmune disease that primarily affects the thyroid gland. It is the most common cause of hyperthyroidism. Genetic studies have shown that human leukocyte antigen (HLA) plays an important role in the development of GD. In this article, we performed a meta-analysis determined to evaluate the relationship between HLA-DRB1 alleles and GD. This meta-analysis included 9 studies (3582 cases in the case group and 23070 cases in the control group) and 27 alleles was performed. The combined results showed that, compared with the control group, GD patients have a significant increase in the frequency of DRB1*1403 (OR=2.50, 95% CI=1.78–3.51, pc<0.0001) and have a significant decrease in frequencies of DRB1* 0101 (OR=0.45, 95% CI=0.34–0.59, pc<0.0001) and DRB1*0701 (OR=0.44, 95% CI=0.35–0.55, pc<0.0001). The meta-analysis indicated that, in Asian populations, DRB1*1403 is a risk allele for GD, and DRB1*0101 and DRB1*0701 are protective against the occurrence of GD. We surprisingly discovered that the susceptibility alleles for GD in Asian populations are completely different from Caucasians and the protective alleles for GD in Asians are quite similar to those of Caucasians. The results of our study may provide new opportunities for gene-targeted therapy for GD in Asian populations.
Keywords: Gravesʼ disease; HLA-DRB1 alleles; Asians; meta-analysis